2018
DOI: 10.1159/000486788
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90-Ibritumomab Tiuxetan (Zevalin®) Radioimmunotherapy after Cytoreduction with ESHAP Chemotherapy in Patients with Relapsed Follicular Non-Hodgkin Lymphoma: Final Results of a Phase II Study

Abstract: Background: Radioimmunotherapy (RIT) is effective in treating relapsed/refractory follicular lymphoma (FL), with durable remissions in first-line consolidation. We hypothesized that RIT with ibritumomab tiuxetan (Zevalin®) would result in durable remissions by eliminating minimal residual disease after cytoreduction. Methods: Patients with FL received 2 cycles of ESHAP (etoposide, methylprednisolone, cytarabine, cisplatin) every 28 days, followed by Zevalin 4–6 weeks later if there was no disease progression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…However, most of the patients (87%) had received chemo‐ and not chemoimmunotherapy prior to consolidation in this trial (Marcus et al , ), and therefore this trial could not determine whether RIT improves the outcome of patients treated with the current standard of anti‐CD20 antibody and chemotherapy, followed by anti‐CD20 antibody maintenance. Nevertheless, several smaller phase II trials have shown an increased CR rate after 90 Y‐IT consolidation (Provencio et al , ; Pisani et al , ; Casadei et al , ; Puvvada et al , ) following induction with CHOP and rituximab (R‐CHOP) as compared to R‐CHOP induction alone. However, a 2‐year maintenance with rituximab or obinutuzumab (Salles et al , ; Marcus et al , ), instead of 90 Y‐IT consolidation, is currently common practice after first line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the patients (87%) had received chemo‐ and not chemoimmunotherapy prior to consolidation in this trial (Marcus et al , ), and therefore this trial could not determine whether RIT improves the outcome of patients treated with the current standard of anti‐CD20 antibody and chemotherapy, followed by anti‐CD20 antibody maintenance. Nevertheless, several smaller phase II trials have shown an increased CR rate after 90 Y‐IT consolidation (Provencio et al , ; Pisani et al , ; Casadei et al , ; Puvvada et al , ) following induction with CHOP and rituximab (R‐CHOP) as compared to R‐CHOP induction alone. However, a 2‐year maintenance with rituximab or obinutuzumab (Salles et al , ; Marcus et al , ), instead of 90 Y‐IT consolidation, is currently common practice after first line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…This also aligns with the incidence of t-MDS/AML in (90)Y-IT studies in relapsed/refractory NHLs which was up to 10% and with (90)Y-IT use as a consolidation therapy following induction chemoimmunotherapy which was 3%. [19][20][21][22][23][24] It appears that the interaction of prior or recent exposure to CIT and (90)Y-IT plays an important role in pathogenesis of t-MDS/AML.…”
Section: Discussionmentioning
confidence: 99%
“…Puvvada also hypothesized that RIT eliminated minimal residual disease after cytoreduction in FL, thus facilitating durable complete remissions. 16 Twenty-eight patients with FL received 2 cycles of ESHAP (etoposide, methylprednisolone, cytarabine, and cisplatin) every 28 days, followed by 90Y-IT 4 to 6 weeks later if there had been no disease progression and <25% bone marrow involvement. The ORR was 72%, with 45% achieving CR.…”
Section: Introductionmentioning
confidence: 99%